2022
DOI: 10.1039/d2sm00643j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salt on the lamellar Lα-to-MLV transformation in SDS/octanol/water under microfluidic flow

Abstract: We investigate the effect of added (NaCl) salt and varying flow rate on the phase behaviour and flow response of a model surfactant Lα phase, sodium dodecyl sulfate (SDS)/octanol/water, using...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Finally, we demonstrate the use of the flow-DLS system in the rapid characterisation of a model micellar surfactant solution with addition of salt, namely SDS/NaCl/water, where R H is obtained over time as the composition changes, within 5 s intervals. Owing to its remote fibre-optic configuration, our flow-DLS can be readily integrated within a lab-on-a-chip system, our coupled in a modular fashion with other techniques such as SANS, 46–50 SAXS, 51,52 Raman spectroscopy, 53 microrheology, 54 viscometry, 38 and many other experimental approaches to complement the spatio-temporal characterisation of complex, reactive or dynamic systems.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we demonstrate the use of the flow-DLS system in the rapid characterisation of a model micellar surfactant solution with addition of salt, namely SDS/NaCl/water, where R H is obtained over time as the composition changes, within 5 s intervals. Owing to its remote fibre-optic configuration, our flow-DLS can be readily integrated within a lab-on-a-chip system, our coupled in a modular fashion with other techniques such as SANS, 46–50 SAXS, 51,52 Raman spectroscopy, 53 microrheology, 54 viscometry, 38 and many other experimental approaches to complement the spatio-temporal characterisation of complex, reactive or dynamic systems.…”
Section: Discussionmentioning
confidence: 99%
“…The phase behaviour and rheology of the L a pseudoquaternary SDS/octanol/brine system has been previously investigated, in particular due to its response to flow near the L a -L 3 phase boundary. 17,18,[21][22][23][24][25][26][27][28] In particular, the 6.5% SDS/7.9% octanol/85.6% brine system has been reported to undergo flow-induced phase transformations from lamellar L a to multilamellar vesicles (MLVs), and ordered MLV arrays of prescribed dimensions at selected temperatures (near ambient) and shear rates. Generally, the addition of NaCl promotes the formation of L 4 -L a -L 3 sequence of phases.…”
Section: Discussionmentioning
confidence: 99%
“…Freyssingeas et al 43 observed an increase in both in d and membrane bending rigidity k in binary C 12 E 5 /water system, rationalised in terms of a decrease in polar headgroup area. While the addition of NaCl to charged surfactants has been shown to decrease the membrane bending rigidity via membrane screening effect at ambient conditions due to charge screening effect, 18,44,45 the increase in temperature will facilitate the dissociation of Na + ions from the SDS in lamellar membrane in presence of brine matrix leading to increase in headgroup repulsions and increase in membrane bending rigidity k. 46 Further, as the Bjerrum length l B increases with temperature, the spatial extent of Coulombic interactions comparatively increases, contributing to an increase in k (see Fig. S5, ESI †), 47…”
Section: Temperature Scan Along Representative Lamellar L a Compositionsmentioning
confidence: 99%